Eksplorasi Potensi Pengembangan Sektor Keuangan Syariah dalam Meningkatkan Inklusi Keuangan di Padangsidimpuan - Nasution, Sahara Bulan (Fakultas Ekonomi dan Bisnis Islam, 2024)
This research aims to examine the potential for developing the sharia financial sector in increasing financial inclusion in Padangsidimpuan City. The Analytic Hierarchy Process (AHP) approach was used with data obtained through surveys and in-depth interviews. The research results show that the main obstacles are limited infrastructure, low human resource competency, and the dominance of the conventional financial sector. The proposed solutions include sharia financial education, technology development, and collaboration with small businesses. This research emphasizes the importance of regulation, technological innovation, and community involvement in expanding access to sharia finance. Future research is recommended to compare the effectiveness of policies in various regions and examine the long-term impact of Islamic financial technology.